CPNE7-Induced Autophagy Restores the Physiological Function of Mature Odontoblasts - Park, Yeoung-Hyun; Son, Chul; Seo, You-Mi; Lee, Yoon Seon; Har, Alix; Park, Joo-Cheol (Frontiers in Cell and Developmental Biology, 2021)
Dentin, which composes most of the tooth structure, is formed by odontoblasts, long-lived post-mitotic cells maintained throughout the entire life of the tooth. In mature odontoblasts, however, cellular activity is significantly weakened. Therefore, it is important to augment the cellular activity of mature odontoblasts to regenerate physiological dentin; however, no molecule regulating the cellular activity of mature odontoblasts has yet been identified. Here, we suggest that copine-7 (CPNE7) can reactivate the lost functions of mature odontoblasts by inducing autophagy. CPNE7 was observed to elevate the expression of microtubule-associated protein light chain 3-II (LC3-II), an autophagy marker, and autophagosome formation in the pre-odontoblast and mature odontoblast stages of human dental pulp cells. CPNE7-induced autophagy upregulated DSP and DMP-1, odontoblast differentiation and mineralization markers, and augmented dentin formation in mature odontoblasts. Furthermore, CPNE7 also upregulated NESTIN and TAU, which are expressed in the physiological odontoblast process, and stimulated the elongation of the odontoblast process by inducing autophagy. Moreover, lipofuscin, which progressively accumulates in long-lived post-mitotic cells and hinders their proper functions, was observed to be removed in recombinant CPNE7-treated mature odontoblasts. Thus, CPNE7-induced autophagy reactivated the function of mature odontoblasts and promoted the formation of physiological dentin in vivo. On the other hand, the well-known autophagy inducer, rapamycin, promoted odontoblast differentiation in pre-odontoblasts but did not properly reactivate the function of mature odontoblasts. These findings provide evidence that CPNE7 functionally reactivates mature odontoblasts and introduce its potential for dentinal loss-targeted clinical applications.